Mechanical scarification increases seed germination of Neltuma alba (Fabaceae), a threatened tree from the Atacama Desert - Humaña, Ana María (2024)
Neltuma alba is a tree whose seeds were probably dispersed by now-extinct animals. Currently, its fruits are consumed by foxes, guanacos, donkeys, and goats, which may scarify the seeds during ingestion, thereby enhancing germination. However, these animals might damage the cotyledons when chewing the fruits, potentially reducing the survival and growth of the plants, although this occurs infrequently. We hypothesize that mechanical scarification of seeds increases their germination but does not affect the survival and growth of the plants. Our objective was to evaluate the effects of mechanical scarification on seed germination and subsequent plant survival. We scarified the seeds by sanding them before sowing them in a nursery with daily watering for six months. Subsequently, the plants were transplanted to the field, where they received daily watering for six months, biweekly watering for the next twelve months, and no watering for the following two years. Seed scarification significantly increased germination by 1.5 times: 58 and 39% germination in scarified and non-scarified seeds, respectively. Scarification did not significantly affect plant survival. Survival rates were 93, 67, 67, and 26% at the end of the first, second, third, and fourth years, respectively. Similarly, scarification did not significantly affect plant height, with plants reaching heights of 28, 59, 74, and 118 cm in the first, second, third, and fourth years, respectively. Understanding the limiting factors for the reproduction of endangered plants in the Atacama Desert is crucial for proposing effective conservation actions.